2007
DOI: 10.1093/cercor/bhm156
|View full text |Cite
|
Sign up to set email alerts
|

Attention and Executive Systems Abnormalities in Adults with Childhood ADHD: A DT-MRI Study of Connections

Abstract: Attention-deficit/hyperactivity disorder (ADHD) is hypothesized to be due, in part, to structural defects in brain networks influencing cognitive, affective, and motor behaviors. Although the current literature on fiber tracts is limited in ADHD, gray matter abnormalities suggest that white matter (WM) connections may be altered selectively in neural systems. A prior study (Ashtari et al. 2005), using diffusion tensor magnetic resonance imaging (DT-MRI), showed alterations within the frontal and cerebellar WM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
177
3
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(202 citation statements)
references
References 73 publications
16
177
3
6
Order By: Relevance
“…WM signal intensities may also show differences that indicate abnormal cerebral myelination. The demonstration of FA abnormalities in adults who had ADHD in childhood provides further support for the persistence of structural abnormalities into adulthood (Makris et al, 2008).…”
Section: Wm Abnormalities In Adhdmentioning
confidence: 73%
See 2 more Smart Citations
“…WM signal intensities may also show differences that indicate abnormal cerebral myelination. The demonstration of FA abnormalities in adults who had ADHD in childhood provides further support for the persistence of structural abnormalities into adulthood (Makris et al, 2008).…”
Section: Wm Abnormalities In Adhdmentioning
confidence: 73%
“…One of the most replicated alterations is a significantly smaller CC, and there are conflicting reports regarding the affected callosal segments (Luders et al, 2009). Moreover, recent magnetic resonance imaging (MRI) structural investigations show that WM alterations are present in children, adolescents and adults with ADHD (Makris et al, 2008). Table 1 presents an overview of white matter abnormalities in ADHD patients from the literature.…”
Section: Wm Abnormalities In Adhdmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most consistent findings from studies of anatomical connectivity, in children and adolescents with ADHD, is reduced fractional anisotropy (Hamilton et al 2008;Makris et al 2008;Luders et al 2009;Konrad et al 2010) of fronto-striatal tracts (within the cortico-striatal network) and fronto-parietal tracts (within the ventral and dorsal attention network). These findings have been supported by some (Dickstein et al 2006;Rubia 2011;Cubillo et al 2012) but not all studies of functional connectivity (Tian et al 2006;Uddin et al 2008).…”
Section: Introductionmentioning
confidence: 89%
“…Further, prefrontal fiber tract measures were associated between ADHD parents and their children, suggesting disruption of frontostriatal connections has a role in ADHD. Makris et al (2008) showed that abnormalities of the cingulum bundle and superior longitudinal fascicle IIFconnection pathways that subserve attention and executive functionsFare evident in adults with ADHD. Lower corticospinal tract and superior longitudinal fasciculus FA (Hamilton et al, 2008) similarly suggested disruption of motor and attention networks in ADHD children, whereas the study by Silk et al (2008) indicated that fronto-striatal and fronto-parietal circuitry abnormalities exist in children with ADHD.…”
Section: Selected Adhd Imaging Datamentioning
confidence: 99%